PELATIHAN PEMBELAJARAN BERBASIS STEAM BAGI GURU LABSCHOOL UNPATTI - Hadi, Hafid Kholidi; Vicky Dwi Wicaksono; Mas Suryanto, H.S; Achmad Kautsar; Andhega Wijaya (Abimanyu : Jornal of Community Engagement, 2025)
The STEAM Learning Training at Labschool UNPATTI aims to enhance teachers' capacity to design and implement an interdisciplinary learning approach that integrates science, technology, engineering, arts, and mathematics. This training combines theoretical material with practical experience, where participants are trained in data processing, scientific article writing, and publication strategies, as well as gaining hands-on skills in designing STEAM projects that meet students' needs for relevant, interactive, and project-based learning. These projects are designed to develop critical 21st-century skills such as critical thinking, creativity, and collaboration. The methods used in this training include lectures, Q&A sessions, discussions, assignments, and independent exercises. The result of this training is an increase in teachers' understanding and skills by 91%. Additionally, teachers found the STEAM learning training helpful in supporting the growth and development of students.